Readability Analysis of Online Health Information on Gestational Diabetes. Issue 1 (2nd January 2023) - Samuel, Lalitha; Fera, Joseph; Basch, Corey H.
Abstract: This study aimed to determine the level of readability of online information on gestational diabetes mellitus (GDM). Readability of 100 English-language websites was assessed by five readability measures: Flesch-Kincaid Grade level (FKGL), Gunning Fox Index (GFI), Coleman Liau Index (CLI), Simple Measure of Gobbledygook (SMOG), and Flesch Reading Ease (FRE). A majority (90%+) of the sample was determined to have unacceptable readability levels, with averages at least one standard deviation away from recommended levels. Not more than a tenth of the websites measured readability to be acceptable or not equivalent to grade seven and above. Results suggest an urgent need for health professionals who create online information related to GDM to revisit and revise the text to be simplified and more readable.